INTEGRATION STRATEGY OF CASE STUDY AND LEARNING BASED PROJECT METHODS IN LEARNING FRENCH AT SMKN 1 BERASTAGI TANAH KARO - Ghofur, Abdul; Polili, Andi Wete; ., Azmi (Journal of Community Research and Service, 2024)
This program is considered important because Indonesia educational system require the use of problem-based learning methods (case studies) and project-based learning. In this regard, French teachers at partner schools find it difficult to teach using these two methods. To apply these two methods, teaching materials that match the characteristics of the two methods used are needed. To solve this problem, We have tried to integrate problem and project based learning methods in a structured textbook. The textbook was obtained through collaboration between lecturers and vocational French teachers. The textbook have been tested in learning classes. Based on the results of the trial, teachers felt very helped by the textbook which was developed through the integration of problem-based learning methods and case studies. In this way, learning becomes more effective and easier to implement. The conclusion from the results of this activity is that the integration of problem and project-based learning methods which are realized in the form of textbooks is very appropriate for use in learning.